THE IMPACT OF WORK ETHIC AND PSYCHOLOGICAL SAFETY ON ORGANIZATIONAL COMMITMENT IN PHARMACEUTICAL COMPANIES PT XYZ IN BEKASI, WEST JAVA - Agung Priyono; Ahmad Fairus Azka; Didip Diandra (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
Pharmaceutical companies are one industry that is expected to provide benefits to the wider community. In carrying out its operational activities, pharmaceutical companies use quite a few assets. PT This can cause PT XYZ to become a bankrupt company which is not good for employee continuity while working. This research aims to examine the influence of work ethic and psychological safety on organizational commitment at PT XYZ. The method that will be used in this research is quantitative, data collection was carried out by distributing questionnaires to 166 respondents and using simple random sampling techniques. The research results show that work ethic has a positive and significant effect on organizational commitment, psychological safety has a positive and significant effect on organizational commitment.